K2Sn2ZnSe6, Na2Ge2ZnSe6, and Na2In2GeSe6: a new series of quaternary selenides with intriguing structural diversity and nonlinear optical properties. Issue 18 (6th April 2016) - Zhou, Molin; Li, Chao; Li, Xiaoshuang; Yao, Jiyong; Wu, Yicheng
Abstract : New selenides K2 Sn2 ZnSe6, Na2 Ge2 ZnSe6, and Na2 In2 GeSe6 exhibit diverse structures and Na2 In2 GeSe6 possesses a moderate second harmonic generation response. Abstract : Three new compounds ( i.e., K2 Sn2 ZnSe6, Na2 Ge2 ZnSe6, and Na2 In2 GeSe6 ) with intriguing structural diversity and nonlinear optical properties were discovered for the first time. They crystallize in space groups P 4/ ncc, I 4/ mcm and Cc, respectively. In K2 Sn2 ZnSe6 and Na2 Ge2 ZnSe6, the [Sn(Ge)Se4 ] tetrahedra and [ZnSe4 ] tetrahedra are linked via edge-sharing to build up a 1D [Sn2 ZnSe6 ] infinite chain separated by K + (Na + ) cations along the c direction, while the structure of Na2 In2 GeSe6 is an interesting three-dimensional framework composed of [InSe4 ] and [GeSe4 ] tetrahedra via corner-sharing with Na + cations in the cavities. The experimental optical band gaps of these compounds were determined as 1.71(2) eV, 2.36(4) eV and 2.47(2) eV, respectively, according to UV-vis-NIR diffuse reflectance spectroscopy. Interestingly, in addition to the large band gap (1.80 eV for AgGaSe2, as a comparison), Na2 In2 GeSe6 exhibits phase-matchable nonlinear optical (NLO) properties with a powder second harmonic generation signal about 0.8 times that of AgGaS2 . Moreover, Na2 In2 GeSe6 melts congruently at a rather low temperature of 671 °C, which suggests that bulk crystals can be easily obtained by the Bridgman–Stockbarger method. Our preliminary results indicate that Na2 In2 GeSe6 has promising applications in IR nonlinear optics.